SOSIALISASI ANCAMAN ERUPSI GUNUNG SLAMET TERHADAP WILAYAH KABUPATEN BANYUMAS-JAWA TENGAH - Asmoro Widagdo; Sachrul Iswahyudi; Anjar Trilaksono; Indra Permana Jati; Gentur Waluyo (Universitas Jenderal Soedirman, 2021)
Slamet volcano is one of the active volcanoes in Central Java which is located on the north side of Banyumas Regency, Central Java. The southern slope of this mountain is a protected forest area, hiking trails to the top and tourist areas. The threat of a volcanic eruption needs to be socialized to residents in areas that have the potential to be affected by an eruption disaster if one day it occurs. Knowledge and awareness of residents and the public visiting tourist areas need to be built through socializing the threat of Mount Slamet eruption. The method used in this community service is through a series of literature review activities, field observations and socialization to the community. Socialization has been carried out to the community of small traders, tourism workers and visitors/tourists.Keywords: mountain, eruption, tourism, community, socialization.